GAS CHROMATOGRAPHY-MASS SPECTROMETRY ANALYSIS AND GROWTH RETARD NATURE OF Barbula lambarenensis ON BACTERIA (FUDMA JOURNAL OF SCIENCES, 2022)
Research studies have shown that mosses contain bioactive substances and are of significant economic importance. The aim of this study was to analyze the composition of Barbula lambarenensis and screen for its bioactivity. The moss collected from its natural habitat was air- dried at room temperature in the laboratory, extracted with methanol and the crude extract was utilized for gas chromatography-mass spectrometry (GC-MS) analysis, antibacterial sensitivity testing and generation time elongation assay. The antimicrobial activity was tested using 12 bacterial strains. The result of the analysis showed the presence of 35 compounds with n-Hexadecanoic acid (22.59%), cis-Vaccenic acid (18.52%), 1,2,4-Cyclopentanetrione, 3-butyl- (13.84%) and 5-Hydroxymethylfurfural (10.24%) as the most abundant compounds. Extract of Barbula lambarenensis did not inhibit growth of test organisms in the antibacterial sensitivity test. Generation time elongation assay showed a reduction in the growth rate of Bacillus cereus and Morganella morganii. The study indicated that Barbula lambarenensis contain numerous compounds with varying bioactivities which can be exploited by the pharmaceutical industry especially in the production of novel medicine.
Keywords: Mosses, Analysis, Extract, Biological activity